Relación entre la ejecución presupuestaria en planeamiento gubernamental y la eficiencia de gestión del Gobierno Regional de Loreto 2014 – 2023 - Guivar Vasquez, Maria Nelly (2025)
Government planning is the set of prospecting actions, diagnosis, formulation of strategies and policies, design of interventions, as well as the development, monitoring and evaluation of programs and projects of the Regional Government of Loreto. Likewise, management encompasses the set of actions developed to optimize the use of human, material and financial resources, aimed at achieving the objectives pursued by the institution, which has five dimensions that are management and superior supervision, advice and support, infrastructure and equipment, preparation and improvement of human resources, and internal control. Through bivariate analysis, the objective has been to determine the relationship between budget execution in government planning and the management efficiency of the Regional Government of Loreto during the period 2014-2023. For this, a total of forty quarterly records have been analyzed and it was found that, the greater the budget execution in government planning, the greater the management efficiency of the institution, justified by a correlation coefficient of 33.81%. With respect to the dimensions of the second variable, only a significant relationship was found between budget execution in government planning and higher management and supervision, and with the preparation and improvement of human resources.